Os direitos da sociobiodiversidade na América Latina e a sustentabilidade de produtos - Silva, Thaís Camponogara Aires da (2019)
In the context of today's environmental crisis, the environment is the central point of a discussion that involves social and informational inequality, environmental injustice, human dignity, economic and developmental interests, colonial relations, territory, environmental impacts resulting from industrial activities and consumption, and serious environmental consequences, which are detrimental to the lives of present and future generations. Add to this the perspective of the Latin American countries, historically exploited and possessing ecological diversity and wealth of originating knowledge. Therefore, we perform a theoretical analysis of the juridical and social aspects involved in this theme, in order to think the possibilities of sustainability products, in its various dimensions, referenced through socio-environmental aspects, in order to contribute to the realization of sociobiodiversity rights in Latin America today, relating human rights and the environment as parts of a whole. Due to the interdisciplinary nature of the research, as a method of approach, the systemic-complex basis theory is used as the theoretical matrix. Regarding the procedure method, a bibliographic research was carried out and, for the data collection technique, the production of extended abstracts and files was adopted. Because it is a theoretical work, its proposal is to think of a way of seeing the world that puts the rights of socio-biodiversity in the forefront, with the achievement of sustainability in all dimensions. And in the context presented, the change in world view and awareness about the environmental issue are already substantial advances, considering the constant human search for quality of life. Finally, it is concluded that technological and economic development is necessary, and Latin American countries, by their position in international relations, seek this development. However, this development must also involve the environmental, social and cultural dimensions, in order to meet sustainability with regulation by the State on the market. Also, the development of products that have a sustainable lifecycle in all its stages, focusing on local needs and the use of resources and knowledge of the place, turning to Latin American peculiarities, without reproducing foreign dominant patterns. It is the practice of the dialogue of knowledge, in a respectful relationship of these cultures and knowledge, which should be valued and encouraged, given the history of negation and past exploitation, in this reoccupation by the original peoples of what always belonged to them, in a suffice to the relations of domination. Moreover, the Latin American countries are immensely rich, but they have a vision of the future in the management of these riches, for conditions worthy of life for the whole population, as well as the preservation of the environment.